The brain‐penetrating, orally bioavailable, ghrelin receptor agonist HM01 ameliorates motion‐induced emesis in Suncus murinus (house musk shrew). (3rd February 2020) - Tu, Longlong; Lu, Zengbing; Ngan, Man P.; Lam, Francis F.Y.; Giuliano, Claudio; Lovati, Emanuela; Pietra, Claudio; Rudd, John A.
Abstract : Background and Purpose: HM01, a novel, orally bioavailable, brain‐penetrating agonist of ghrelin receptors, ameliorates emesis in Suncus murinus . This study compared HM01's activity against motion sickness with that of the less brain‐penetrating ghrelin receptor agonist, HM02. Experimental Approach: The potential of HM01 and HM02 to relax isolated mesenteric arteries and to increase feeding was investigated. Radio telemetry was used to record gastric slow waves and body temperature. Plethysmography was used to measure respiratory function. HM01 and HM02 were administered p.o. 1 hr prior to provocative motion, and c‐Fos expression in brain sections was assessed. Key Results: HM01 and HM02 both relaxed precontracted arteries, yielding EC50 values of 2.5 ± 0.5 and 3.5 ± 0.4 nM respectively. HM01 increased feeding, but HM02 did not. Both compounds caused hypothermia and bradygastria. Motion induced 123 ± 24 emetic events. HM01, but not HM02, reduced motion‐induced emesis by 67.6%. Motion increased c‐Fos expression in the nucleus tractus solitarius (NTS), dorsal motor nucleus of the vagus (DMNV), medial vestibular nucleus (MVe), central nucleus of the amygdala, and paraventricular hypothalamic nucleus (PVH). HM01 alone increased c‐Fos expression in the area postrema, NTS, DMNV, PVH, and arcuate hypothalamic nucleus; HM02 had a similar pattern except it did not increase c‐Fos in the PVH. Both compounds antagonized the motion‐induced increases in c‐Fos expression in the MVe. Conclusions and Implications: HM01 is more effective than HM02 in preventing motion‐induced emesis. The difference in potency may relate to activation of ghrelin receptors in the PVH.